Direct investment of the United States in Peru, 1971-1987: A sobering review - Ruiz de Castilla, Verónica (1990)
​In the context of a deteriorating economic situation in Peru, the necessity of obtaining foreign savings through foreign investment is becoming increasingly important. The article examines the various legal frameworks that have ruled Direct Foreign Investment (IED) in Peru, analyzes their effects on the flows and stock of IED from the United States, and finishes by presenting alternatives to improve the investment relationship between the two countries.​